Advances in Transarterial Radionuclide Therapy for Hepatocellular Carcinoma and Other Liver Tumors: From Yttrium-90 Radioembolization to Emerging Lipiodol-Based Theranostic Approaches - Yumiko Kono; Keita Utsunomiya; Shuji Kariya; Noboru Tanigawa (Molecules, 2026)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related mortality, and internal radionuclide therapy is an important locoregional option for unresectable disease. This review summarizes the current landscape of transarterial radionuclide therapy for HCC and, as a translational perspective, considers how the carrier, radionuclide, and dosimetry concepts established in HCC may extend to secondary liver tumors (liver metastases). It begins with established transarterial radioembolization (TARE/selective internal radiation therapy, SIRT) using yttrium-90 (90Y) microspheres and the shift toward personalized dosimetry and combination with systemic and immune-based therapies. It then examines alternative radionuclides and carrier systems—including holmium-166 (166Ho) microspheres, iodine-131 (131I) lipiodol, rhenium-188 (188Re) lipiodol, and lutetium-177 emulsified in lipiodol (177Lu-lipiodol)—from the standpoint of their physical properties, radiochemistry, theranostic potential, and preclinical and clinical evidence. Particular attention is given to 177Lu-based approaches, including their favorable beta energy, the concurrent imageable gamma emission that enables single-photon emission computed tomography (SPECT)-based dosimetry, and the potential to address post-embolization hypoxia-related radioresistance, while noting that the clinical evidence for 177Lu-lipiodol remains preclinical. The application of these platforms to colorectal and neuroendocrine liver metastases is then outlined. Finally, regulatory, radiation safety, and waste management considerations and the principal challenges to clinical translation are discussed.